氷上からの湖底・海底堆積物掘削プロジェクトの報告（JARE-58/59） - 菅沼, 悠介; スガヌマ, ユウスケ; 田邊, 優貴子; タナベ, ユキコ; 香月, 興太; カツキ, コウタ; 柴田, 大輔; シバタ, ダイスケ; 川又, 基人; カワマタ, モト; Suganuma, Yusuke; Tanabe, Yukiko; et al. (国立極地研究所, 2018)
第58/59 次日本南極地域観測隊（JARE-58/59）の活動の一部として，2017—2018 の夏期に，宗谷海岸エリアにおいて凍結した湖面/ 海面上からの湖底・海底堆積物の掘削を行った．本調査チームのメンバー構成は，JARE58 越冬隊の生物隊員1 名と，JARE59 の先遣隊として派遣された地形隊員2 名および生物隊員2 名である．JARE59 の先遣隊の南極大陸へのアクセスについては，ドロンイングモードランド航空ネットワーク（Dronning Maud Land Air Network:DROMLAN）の提供する航空網を利用した．ただし，往路についてはDROMLANフライトスケジュールの混乱の影響を受けて，急遽Norwegian Polar Institute（NPI）が提供する大陸間フライトを利用することとなった．結果として，トロール基地およびノボラザレフスカヤ基地滑走路を経由して，11 月上旬に昭和基地に到達した．また，海氷上の移動が困難になる11 月後半～「しらせ」到着までの間，スカルブスネスきざはし浜小屋にて本調査チームは孤立するため，この間JARE58 越冬隊より医療隊員が調査に同行した．調査期間中，新たに開発した可搬型パーカッションピストンコアラーを用いて，西オングル島，ラングホブデ，スカルブスネス，およびスカーレンの各地の湖沼および浅海域の23 地点から，計26 本の堆積物試料を採取した．本稿では，氷上からの湖底・海底堆積物掘削プロジェクトの概要と，DROMLAN フライトスケジュールの混乱への対応を含めた先遣隊としての行動全般について報告する． Lake and marine sediment coring were carried out in the Soya Coast in East Antarctica, during the 2017–2018 summer season as part of the 58/59th Japanese Antarctic Research Expedition (JARE). The field party consisted of one biologist from the JARE58 wintering team, two geomorphologists and two biologists from an advance team of the JARE59 summer members. Airborne access to Antarctica for the advance team was provided by Dronning Maud Land Air Network (DROMLAN). However, a continental flight for the outward way was carried out by the Norwegian Polar Institute (NPI) due to a trouble of scheduling of DROMLAN flights. Consequently, the JARE 59 members arrived at Syowa station via Troll station and Novolazarevskaya Airbase in early November 2017.Because the field team was isolated in the Kizahashi hut from late November until the arrival of Shirase due to sea ice conditions, one medical doctor also joined the field party. In total 26 sediment cores were obtained from 23 lakes and shallow marine sites in West Ongul, Langhovde, Skarvsnes, and Skallen area using the newly developed portable piston corer. This report summarizes activities of this field expedition including fieldwork, logistics, and weather observation. departmental bulletin paper